What is derivative f(x)=(-y-sin(x^3))?
1 Answer | Add Yours
You need to replace y for f(x), such that:
`y = -y - sin(x^3)`
You need to move the terms that contain y to the left side, such that:
`2y = -sin(x^3) => y = -(sin(x^3))/2`
You need to differentiate the function with respect to x, using the chain rule, such that:
`(dy)/(dx) = -(1/2)*(d(sin(x^3)))/(dx)*(d(x^3))/(dx)`
`(dy)/(dx) = -(1/2)*cos(x^3)*(3x^2)`
Hence, evaluating the derivative of the given function, using the chain rule, yields `(dy)/(dx) = -(3x^2*cos(x^3))/2` .
Join to answer this question
Join a community of thousands of dedicated teachers and students.Join eNotes